The Negative Impact of Some Influencers’ Content on Social Media in Mauritania: A Descriptive and Analytical Study - Sidi, Ahmed (Journal of Humanities & Social Sciences, 2025)
This study addressed the negative impacts of the content of some influencers on social media in Mauritania, using a descriptive approach to understand this phenomenon in its local context.The study relied on the tools of surveys and interviews to collect quantitative and qualitative information to enhance the added value of the study, with the aim of assessing the role of influencers in affecting values and morals, and promoting products that may be harmful to health, in addition to disseminating misleading information. The results showed that 88% of the participants believe that the content published by some influencers negatively affects values and morals, while 82% confirmed that the influencers' publication of inaccurate or misleading information contributes to the widespread dissemination of this information among social media platform users. 75% of those covered by the study believed that influencers promote products that may be harmful to health. The study also indicated that TikTok is considered the most dangerous platform, with 85% believing that it poses a major threat to societal values due to the nature of the content spread on it. Based on these results, the study recommends establishing a legal framework to regulate the work of influencers, standards to control advertising on influencers' pages, and creating a national platform to verify news, in addition to encouraging positive content that enhances cultural and social values.The study also emphasizes the need to develop educational curricula to be more adaptable to rapid digital changes, and to strengthen the partnership between the government and technology companies to regulate digital content more effectively.
Keywords: social media networks; digital content; Influencers; Mauritanian digital platforms; media misinformation